Female Dispersion Is Necessary, but Not Sufficient, for Pairbonded Monogamy in Mammals - Dunbar, R. I. M. (Frontiers in Ecology and Evolution, 2022)
Explanations for the evolution of social monogamy in mammals typically emphasise one of two possibilities: females are overdispersed (such that males cannot defend access to more than one female at a time) or males provide a service to the female. However, the first claim has never been formally tested. I test it directly at three levels using population-level data from primates and ungulates. First, I show that the females of monogamous genera do not have territories that are significantly larger, either absolutely or relatively, than those of polygynous genera. Second, using two indices of territorial defendability, I show that, given their typical day journey lengths, males of most monogamous species could easily defend an area large enough to allow them to monopolise as many as 5-10 females when these ranged solitarily. Finally, I use a model of male mate searching strategies to show that the opportunity cost incurred by monogamous males is typically 5-10 times the reproductive success they actually obtain by being obligately monogamous. This suggests that the selection pressure dissuading them from pursuing a roving male strategy must be very considerable. At present, the evidence is undecided as to whether mitigating predation or infanticide risk is the primary function, but estimates of their impacts suggest that both are in fact plausible.